Laterality preferences in athletes: Insights from a database of 1770 male athletes - Wang, W.-C.; DeLang, M.; Vittetoe, K.; Ramger, B.; Hilbig, S.; Appelbaum, L. G. (American Journal of Sports Science, 2018)
Laterality preferences are inherent in most sensory and motor activities, and sports are certainly one domain wherein these preferences might impact performance and outcomes. The fact that most individuals exhibit laterality preferences and that sporting demands differentially draw on these abilities makes the expression of these preferences in athletes a topic ripe for exploration. To fill this gap, the current report describes hand, foot, and eye laterality preferences in a large cohort of 1770 male athletes tested on the Nike Sensory Station assessment battery. Self-reported hand and foot preferences, as well as eye dominance measured through the Miles Test, were compared across athletes of different experience levels (middle/high school, college, professional athletes) and primary sports (baseball, basketball, football, hockey, soccer) to evaluate group differences in laterality preferences. Results revealed group differences, most notably a higher proportion of left-hand and left-foot preferences in professional baseball players. These findings offer new insight into the associations among laterality preferences in a large and diverse population of athletes.